2021
DOI: 10.3389/fphys.2021.727000
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Decreased Excitability and Altered Action Potential Characteristics of Cardiac Vagal Neurons in Mice

Abstract: Background: Secondhand smoke (SHS), a major indoor pollutant, is a significant risk factor for cardiovascular morbidity and mortality including arrhythmias and sudden cardiac death. Exposure to SHS can produce autonomic imbalance, as evidenced by reduced heart rate variability (HRV)—a clinical metric of cardiac vagal regulation. Currently, the mechanisms through which SHS changes the vagal preganglionic neuronal inputs to the heart to produce this remains unknown.Objectives: To characterize the effect of SHS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…Our previous study showed that 4 weeks of SHS exposure, at the same concentration as the present study, resulted in a decreased neuronal input-output relationship of these cardiac vagal neurons (Sun et al, 2021). The reduced neuronal output is due to a higher voltage/current threshold required for action potential generation and lower spiking responses to depolarizing stimuli (Sun et al, 2021). This SHS exposure-induced decrease in neuronal output may be a general feature of particulate matter pollution as exposures to particulate matters in the form of iron-soot also decreased HRV and neuronal outputs of these cardiac vagal neurons (Pham et al, 2009).…”
Section: Figuresupporting
confidence: 66%
See 3 more Smart Citations
“…Our previous study showed that 4 weeks of SHS exposure, at the same concentration as the present study, resulted in a decreased neuronal input-output relationship of these cardiac vagal neurons (Sun et al, 2021). The reduced neuronal output is due to a higher voltage/current threshold required for action potential generation and lower spiking responses to depolarizing stimuli (Sun et al, 2021). This SHS exposure-induced decrease in neuronal output may be a general feature of particulate matter pollution as exposures to particulate matters in the form of iron-soot also decreased HRV and neuronal outputs of these cardiac vagal neurons (Pham et al, 2009).…”
Section: Figuresupporting
confidence: 66%
“…Together, these data suggest that the parasympathetic nervous system may be more sensitive to SHS exposure with a faster onset and that continued exposure may further tip the balance of autonomic regulation towards more permanent dysfunction through activation of the sympathetic nervous system. The parasympathetic regulation of the heart is mediated by innervations from the cardiac vagal neurons located in the nucleus ambiguous (Corbett et al, 1999;Pham et al, 2009;Sun et al, 2021). Our previous study showed that 4 weeks of SHS exposure, at the same concentration as the present study, resulted in a decreased neuronal input-output relationship of these cardiac vagal neurons (Sun et al, 2021).…”
Section: Figuresupporting
confidence: 57%
See 2 more Smart Citations
“…Operating principle is to use a certain transient high voltage and strong current through the chest wall directly acting on the heart, so that most or even all of the myocardial cells instantaneous depolarization. The electrical activity of the heart stops instantly, so that the heart is redominated by the highest self-regulatory pacing point, namely, the sinus node, and the abnormal heart rhythm is transformed into the normal sinus rhythm [ 17 , 18 ]. Cardiac surgery mainly improves the abnormal function of the heart to return to normal rhythm by directly cutting the tissue used for sinus velocity generation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%